ANALISIS AMANAT PUPULAN CERPEN BOR KARYA I.B.W. WIDIASA KENITEN - Gunawan, I Wayan Adi (Humanis, 2013)
Research on the short stories Julia, Jro Bukit, Natab, Ayu Bali, dan Pabesen masterpiece I. B. W. Widiasa Keniten aimed to describe the structure of narrative and knowing the message conveyed by the author through his literary masterpiece. In this analysis theory used is structural theory proposed by Luxemburg.dkk, Nurgiyantoro and Teeuw and the other literary experts. Methods and techniques of research is divided into three stages, namely: in providing data using observational methods aided with technical notes and translation techniques. At the stage of data analysis using qualitative methods are assisted with descriptive analytic techniques. Stage presentation of the results of data analysis using descriptive informal methods are assisted with deductive-inductive techniques. The results of this study are can describe the structure of the short story Julia, Jro Bukit, Natab, Ayu Bali, dan Pabesen which consists of the incident, plot, character and characterization, setting, and theme. While the mandate of the analysis carried out in a separate chapter to obtain general and specific mandate. The specific mandate which consists of the mandate of tattwa / philosophy, mandate on ethics / morality, mandate of the ceremony, mandate of the fidelity, and mandate of the social critic.
Keywords: short stories, structure and mandate.